The In Vivo Radiosensitizing Effect of Gold Nanoparticles Based MRI Contrast Agents. Issue 6 (4th February 2014) - Miladi, Imen; Alric, Christophe; Dufort, Sandrine; Mowat, Pierre; Dutour, Aurélie; Mandon, Céline; Laurent, Gautier; Bräuer‐Krisch, Elke; Herath, Nirmitha; Coll, Jean‐Luc; Dutreix, Marie; Lux, François; et al.
<x xml:space="preserve">Abstract</x> The gadolinium chelate coated gold nanoparticles (Au@DTDTPA‐Gd50) which were designed as contrast agents for magnetic resonance imaging (MRI) also behave as radiosensitizers. Their follow‐up by MRI allows determining the delay between the irradiation of the tumor and the injection of the nanoparticles. As a result, the use of Au@DTDTPA‐Gd50 nanoparticles leads to the improvement of the effect of radiotherapy. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>